SMU celebrates first batch of SMU warriors scholarship graduates completing postgraduate degrees with flying colours and prepared for second careers - Singapore Management University (Institutional Knowledge at Singapore Management University, 2015)
The Singapore Management University (SMU) has more reasons to celebrate in Singapore’s golden jubilee year, besides SMU’s 15th anniversary – it saw the inaugural batch of graduates from the first-of-its-kind SMU Warriors Scholarship (SWS) ahead of Singapore’s 50th National Day. These ‘warriors’ are retiring Singapore Armed Forces (SAF) personnel, aged around 50, who commenced SMU postgraduate studies last year and completed their studies this year. Four of the ‘warrior’ graduates celebrate their 50th birthday with the nation this year.